Randomized Controlled Trial of Conventional Versus MicroNet-Covered Stent in Carotid Artery Revascularization - Karpenko, Andrey; Bugurov, Savr; Ignatenko, Pavel; Starodubtsev, Vladimir; Popova, Irina; Malinowski, Krzysztof; Musialek, Piotr (JACC. Cardiovascular interventions, 2021)
The aim of this study was to compare procedure-related ipsilateral cerebral embolism with a conventional (Acculink, Abbott Vascular) versus a MicroNet-covered (CGuard, InspireMD) stent in carotid artery stenting (CAS). The MicroNet-covered stent may reduce periprocedural cerebral embolism in CAS, but level 1 evidence is lacking. A total of 100 consecutive patients were randomized 1:1 to filter-protected CAS using the Acculink or the CGuard device. The study was powered for its primary endpoint of at least 50% reduction in ipsilateral diffusion-weighted magnetic resonance imaging lesion average volume 48 hours postprocedure (blinded external core laboratory analysis). The baseline characteristics of the study groups were similar. Eighty-two (total volume = 18,212 mm3) diffusion-weighted magnetic resonance imaging postprocedural cerebral lesions occurred in 26 Acculink-treated patients and 45 lesions (total volume = 3,930 mm3; 78.4% reduction) in 25 CGuard-treated patients. New cerebral lesion average volume was 171 mm3 vs 73 mm3 (P = 0.017) per affected patient and 222 mm3 vs 84 mm3 (P = 0.038) per lesion (Acculink vs CGuard). In lesion-affected patients, the average sum of lesion volumes was 701 mm3 vs 157 mm3 (P = 0.007). The Acculink significantly increased the risk for multiple (≥5) cerebral lesions (relative risk: 7.8; 95% CI: 1.3-14.9; P = 0.021). At 30 days, new permanent (fluid-attenuated inversion recovery) lesion prevalence was 3:1 (P < 0.001), with total permanent lesion volume 7,474 mm3 vs 574 mm3 (92.3% reduction with the CGuard). There were 6 vs 0 new ipsilateral lesions (P = 0.030) and 2 versus 0 strokes. The MicroNet-covered stent significantly reduced periprocedural and abolished postprocedural cerebral embolism in relation to a conventional carotid stent. This is consistent with the MicroNet-covered stent’s sustained embolism prevention, translating into cerebral protection not only during but also after CAS. The present findings may influence decision making in carotid revascularization. (The SIBERIA Trial [Acculink™ Versus CGuard™]; NCT03488199) [Display omitted]